PERAN KEPUASAN PELANGGAN MEMEDIASI PENGARUH KUALITAS PRODUK TERHADAP NIAT BELI ULANG (Studi pada Produk Pakaian Toko Pusat Baju Bali Murah) - Made Gea Sabrina Diantara; Ni Wayan Sri Suprapti (NETIZEN: JOURNAL OF SOCIETY AND BUSSINESS, 2025)
This study aims to analyze the effect of product quality on repurchase intention through customer satisfaction at Pusat Baju Bali Murah. The research is grounded in the importance of customer loyalty in maintaining business sustainability amid the sales decline caused by the COVID-19 pandemic. A quantitative approach was employed using a survey method involving 100 respondents who had previously purchased from Pusat Baju Bali Murah. Data were analyzed using path analysis and Sobel test to examine mediation effects. The results indicate that product quality has a positive and significant effect on both customer satisfaction and repurchase intention. Moreover, customer satisfaction also significantly influences repurchase intention. The mediation test shows that customer satisfaction partially mediates the relationship between product quality and repurchase intention. Hence, improving product quality not only enhances customer satisfaction but also directly and indirectly encourages repeat purchases. These findings provide valuable insights for MSMEs to strengthen competitiveness through consistent product quality strategies centered on customer satisfaction.